Jewish cultural and religious factors and uptake of population‐based BRCA testing across denominations: a cohort study. (25th November 2021) - Reisel, D; Burnell, M; Side, L; Loggenberg, K; Gessler, S; Desai, R; Sanderson, S; Brady, AF; Dorkins, H; Wallis, Y; Jacobs, C; Legood, R; et al.
Abstract : Objective: To evaluate the association of Jewish cultural and religious identity and denominational affiliation with interest in, intention to undertake and uptake of population‐based BRCA (Breast Cancer Gene) ‐testing. Design: Cohort‐study set within recruitment to GCaPPS‐trial (ISRCTN73338115). Setting: London Ashkenazi‐Jewish (AJ) population. Population or sample: AJ men and women, >18 years. Methods: Participants were self‐referred, and attended recruitment clinics (clusters) for pre‐test counselling. Subsequently consenting individuals underwent BRCA testing. Participants self‐identified to one Jewish denomination: Conservative/Liberal/Reform/Traditional/Orthodox/Unaffiliated. Validated scales measured Jewish Cultural‐Identity (JI) and Jewish Religious‐identity (JR). Four‐item Likert‐scales analysed initial 'interest' and 'intention to test' pre‐counselling. Item‐Response‐Theory and graded‐response models, modelled responses to JI and JR scales. Ordered/multinomial logistic regression modelling evaluated association of JI‐scale, JR‐scale and Jewish Denominational affiliation on interest, intention and uptake of BRCA testing. Main outcome measures: Interest, intention, uptake of BRCA testing. Results: In all, 935 AJ women/men of mean age = 53.8 (S.D = 15.02) years, received pre‐test education and counselling through 256 recruitment clinic clusters (median cluster size = 3). Denominational affiliations included Conservative/Masorti = 91 (10.2%); Liberal = 82 (9.2%), Reform = 135 (15.1%), Traditional = 212 (23.7%), Orthodox = 239 (26.7%); and Unaffiliated/Non‐practising = 135 (15.1%). Overall BRCA testing uptake was 88%. Pre‐counselling, 96% expressed interest and 60% intention to test. JI and JR scores were highest for Orthodox, followed by Conservative/Masorti, Traditional, Reform, Liberal and Unaffiliated Jewish denominations. Regression modelling showed no significant association between overall Jewish Cultural or Religious Identity with either interest, intention or uptake of BRCA testing. Interest, intention and uptake of BRCA testing was not significantly associated with denominational affiliation. Conclusions: Jewish religious/cultural identity and denominational affiliation do not appear to influence interest, intention or uptake of population‐based BRCA testing. BRCA testing was robust across all Jewish denominations. Tweetable abstract: Jewish cultural/religious factors do not affect BRCA testing, with robust uptake seen across all denominational affiliations. Tweetable abstract: Jewish cultural/religious factors do not affect BRCA testing, with robust uptake seen across all denominational affiliations.